2017
DOI: 10.1097/01.aog.0000514269.02935.c1
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postpartum Contraception in Adolescents: Intention, Retention, and Repeat Pregnancies [35A]

Abstract: INTRODUCTION: Rapid repeat pregnancy (within 2 years) among young women poses serious health consequences. Long-acting reversible contraception (LARC) is safe and effective, and available to women immediately postpartum at our institution. Our primary aim was to compare the rapid repeat pregnancy rate for young women (aged 13-24 years) initiating LARC immediately postpartum versus initiating LARC within 8 weeks of delivery, and LARC versus other contraceptive methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…3,4 These studies have found that providing contraception, specifically access to long-acting reversible contraception (LARC) methods, such as the etonogestrel (ENG) contraceptive implant, before hospital discharge can increase utilization and decrease RRP rates. [4][5][6][7][8] Despite this evidence, the implementation of immediate postpartum LARC presents its own challenges. Given the global reimbursement for obstetrical care, bundling of other inpatient procedures and the cost of stocking devices can be cost-prohibitive for hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 These studies have found that providing contraception, specifically access to long-acting reversible contraception (LARC) methods, such as the etonogestrel (ENG) contraceptive implant, before hospital discharge can increase utilization and decrease RRP rates. [4][5][6][7][8] Despite this evidence, the implementation of immediate postpartum LARC presents its own challenges. Given the global reimbursement for obstetrical care, bundling of other inpatient procedures and the cost of stocking devices can be cost-prohibitive for hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Access to ENG contraceptive implant was prioritized given the preference of this LARC method in the adolescent population. [4][5][6][7][8]…”
Section: Introductionmentioning
confidence: 99%